Living standards in Angola, 1760-1975 - Hélder Carvalhal; Nuno Palma (African Economic History Network (AEHN), 2024)
We investigate the well-being of urban workers in Angola under colonialism. Using a newly compiled dataset derived from archival and secondary sources, we construct welfare ratios for both skilled and unskilled workers in the cities of Luanda and Benguela spanning the years 1760 to 1975. Angolan workers experienced lower economic prosperity compared to their counterparts in other regions worldwide. Living standards declined throughout the 19th century, only to recover in the 20th century, particularly from the mid-1960s onward. These patterns can be attributed to variation in the presence of various labor market distortions over time.
Keywords: N17; N37; N97; 330; Living standards; well-being; Angola; colonialism